Randomised trial on pain reduction in hysterosalpingography - a modified technique without vulsellum forceps - Omidiji, Olubukola; Olowoyeye, Omodele; Efidi, Richard; Adegbola, Omololu; Toyobo, Oluyemisi; Okeke, Ogonna; Opara, Thaddaeus; Shabi, Abidemi (The ASEAN Journal of Radiology, 2022)
ABSTRACT Background: Pain is the most common side effect of hysterosalpingography (HSG) and partly arises from vulsellum placement on the cervix and cervical traction. Objective: To study the effect of conducting HSG without grasping the cervix with vulsellum forceps on the time taken to complete the procedure, pain experienced by the participants and diagnostic quality of HSG images produced. Materials and Methods: A randomized controlled trial of 64 consenting adult women referred to the Radiodiagnostic department for HSG from July to December 2020 was carried out. The women were consecutively selected and randomly distributed into two groups: Group 1 - no cervical grasp and Group 2 – with cervical grasp with vulsellum forceps. HSG was done using a fluoroscopy machine, following the standard hospital protocol with speculum, Leech Wilkinson cannula and Urografin 76%. Procedure time, procedure pain using the visual analog scale and diagnostic quality of images were assessed. Data analysis was done using Microsoft Excel and SPSS software version 22. Results: The overall mean duration of the procedure was 12.59 minutes. There was no significant difference in the procedure duration between both groups. The overall mean pain scores immediately and 15 minutes after the procedure were 4.83 and 2.23 respectively. Significant differences in pain scores were seen in the immediate post procedure 3.94 (group 1) versus 5.72 (group 2) and 15 minutes post procedure 1.75 (group 1) versus 2.72 (group 2). After adjusting for confounders, the pain score was noted to be significantly related to the HSG technique with vulsellum use associated with the higher immediate post HSG pain score. No significant difference was seen in the diagnostic image quality between group I and II Conclusion: The elimination of vulsellum forceps during hysterosalpingography was associated with reduced pain in the immediate and 15 minutes after the procedure, without significantly increasing the procedure duration. It had no deleterious effect on the image quality.